2020
DOI: 10.1111/eci.13427
|View full text |Cite
|
Sign up to set email alerts
|

The De Ritis ratio as prognostic biomarker of in‐hospital mortality in COVID‐19 patients

Abstract: Increased concentrations of serum aspartate transaminase (AST) and alanine transaminase (ALT) are common in COVID‐19 patients. However, their capacity to predict mortality, particularly the AST/ALT ratio, commonly referred to as the De Ritis ratio, is unknown. We investigated the association between the De Ritis ratio on admission and in‐hospital mortality in 105 consecutive patients with coronavirus disease of 2019 (COVID‐19) admitted to three COVID‐19 referral centres in Sardinia, Italy. The De Ritis ratio w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 44 publications
9
76
3
1
Order By: Relevance
“…Nineteen studies defined outcomes as disease severity 22 , 27 30 , 37 39 , 42 , 43 , 46 50 , 58 , 60 , 62 , 63 . Seventeen studies defined outcomes as death 21 , 33 , 40 , 44 , 45 , 51 57 , 59 , 65 68 . Four studies used both disease severity and death 26 , 41 , 61 , 64 .…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies defined outcomes as disease severity 22 , 27 30 , 37 39 , 42 , 43 , 46 50 , 58 , 60 , 62 , 63 . Seventeen studies defined outcomes as death 21 , 33 , 40 , 44 , 45 , 51 57 , 59 , 65 68 . Four studies used both disease severity and death 26 , 41 , 61 , 64 .…”
Section: Resultsmentioning
confidence: 99%
“…After full-text review of the remaining 78 articles, a further 11 studies were excluded because they did not meet the inclusion criteria. Thus, 67 studies were included in the meta-analysis [ 20 86 ]. The characteristics of these studies, all published in 2020, are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies were prospective [ 29 , 41 , 52 ], 51 retrospective [ 20 28 , 30 34 , 36 39 , 42 46 , 48 51 , 53 , 54 , 57 60 , 62 , 63 , 65 , 66 , 69 76 , 78 , 80 , 81 , 83 86 ], while 13 did not specifically declare the study design [ 23 , 35 , 40 , 47 , 55 , 56 , 61 , 64 , 67 , 68 , 77 , 79 , 82 ]. Fifty-two studies (77.6%) were performed in China [ 22 , 24 26 , 28 31 , 33 35 , 37 43 , 46 57 , 59 , 62 – 64 , 68 85 ] while the remaining 15 were conducted in the rest of the world [ 20 , 21 , 23 , 27 , 32 , 36 , 44 , 45 , 58 , 60 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study found that the ratio of AST/ALT was a predictor for hospital mortality in patients with COVID-19 [ 30 ]. However, our study did not find any significant difference in the ratio of AST/ALT in patients with oxygen therapy and the ones without.…”
Section: Discussionmentioning
confidence: 99%